PENGGUNAAN TELEPON SELULER UNTUK PEMASARAN SERTA DAMPAKNYA TERHADAP KESEJAHTERAAN PETANI - Feryanto, Feryanto; Rosiana, Nia (Jurnal AGRISEP, 2021)
The development of information technology has encouraged farmers to be able to use cellular phones to support agricultural activities. However, only a few farmers use their cellphones for marketing activities. This study aims to analysis factors influence farmers to use cell phones in marketing activities, and whether cell phone use has an impact on farmers' welfare. The analytical method used is the logit regression model and Propensity Score Matching (PSM). The results showed that what influenced farmers' decisions to use cellular phones for marketing activities were gender, marital status, number of adult household members, education, land ownership status, land area, and counseling. Meanwhile, the impact of the use of cellular telephones, shows that the average farm farmers receive higher treatment compared to the control farmers group.